Risk factors for complications of pancreatic extracorporeal shock wave lithotripsy - Li, Bai-Rong; Liao, Zhuan; Du, Ting-Ting; Ye, Bo; Zou, Wen-Bin; Chen, Hui; Ji, Jun-Tao; Zheng, Zhao-Hong; Hao, Jun-Feng; Jiang, Ying-Yi; Hu, Liang-Hao; Li, Zhao-Shen (Endoscopy, 2014)
Background and study aims: Extracorporeal shock wave lithotripsy is recommended as treatment for stones in chronic pancreatitis. The aim of this study was to investigate the risk factors for complications of pancreatic extracorporeal shock wave lithotripsy (P-ESWL).Patients and methods: Patients with painful chronic pancreatitis and pancreatic stones (> 5 mm diameter) who were treated with P-ESWL between March 2011 and June 2013 were prospectively included. Adverse events after P-ESWL were classified as complications and transient adverse events, depending on severity. The major complications of P-ESWL included post-ESWL pancreatitis, bleeding, infection, steinstrasse, and perforation. Multivariate analyses based on univariate analysis were performed to detect risk factors of overall and moderate-to-severe complications.Results: A total of 634 patients underwent 1470 P-ESWL procedures. The overall complication rate was 6.7 % of all procedures. Complications occurred in 62 patients (9.8 %) after the first ESWL procedure. The risk factors for complications were pancreas divisum (odds ratio [OR] 1.28) and the interval between diagnosis of chronic pancreatitis and P-ESWL (OR 1.28). Protective factors were male sex (OR 0.50), diabetes (OR 0.45), and steatorrhea (OR 0.43). Male sex, the only identified predictor for moderate-to-severe complications, was a protective factor (OR 0.19). For the second P-ESWL procedure, complications occurred in 22/409 patients (5.4 %). Complication and asymptomatic hyperamylasemia after the first ESWL session were significantly associated with higher risk for complications after the second ESWL session (P < 0.05).Conclusions: Patient-related factors were important in determining a high risk of P-ESWL complications when no procedure-related factors were identified. Patients suffering from complications after the first ESWL session were also likely to experience complications in subsequent P-ESWL sessions.